Intensitas Penggunaan Smartphone dan Komunikasi Interpersonal Orangtua Dengan Anak Selama Belajar Daring - Iska Netti (Happiness: Journal of Psychology and Islamic Science, 2022)
In the current situation of the Covid-19 pandemic, make student learning at home. This makes the use of smartphones in online learning activities more intense. As a result, parents need to be wise in determining the use of smartphones so that the intensity of their use does not negatively affect children when they are studying online at home, e.g. B. Make children negligent and postpone class or work. The aim of this study is to determine the intensity of smartphone use as a factor that influences interpersonal communication between parents and children. The study obtained the data from 80 respondents who had children who were currently in elementary school and who attended online schools during the pandemic in Bukitinggi city. The method used in this research is the indigenous science questions method using the Google form. The results of the study show that the intensity of smartphone use is a factor that influences interpersonal communication between parents and children. Implementing guidelines from parents to set a schedule for using smartphones can improve interpersonal communication between parents and children.